2009
DOI: 10.1007/s12640-009-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline is Neuroprotective Against Nigral Dopaminergic Degeneration by a Dual Mechanism Involving MMP-3

Abstract: In Parkinson disease (PD), the dopaminergic (DAergic) neurons in the substantia nigra undergo degeneration. While the exact mechanism for the degeneration is still not completely understood, neuronal apoptosis and inflammation are thought to play roles. We have recently obtained evidence that matrix metalloproteinase (MMP)-3 plays a crucial role in the apoptotic signal in DAergic cells as well as activation of microglia. The present study tested whether doxycycline might modulate MMP-3 and provide neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 49 publications
(55 reference statements)
1
56
0
1
Order By: Relevance
“…MMP-3 was also involved in caspase-3 activation, specifically in apoptotic signaling upstream of caspase-3 and downstream of c-Jun N-terminal kinases. 238,[241][242][243][244] Second, MMP-3 might potentially be involved in a-synuclein cleavage. Sung et al 245 showed that MMP-3 cleaves purified a-synuclein in vitro and that a-synuclein aggregation increased in the presence of MMP-3-cleaved a-synuclein fragments compared to a solution without these fragments.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…MMP-3 was also involved in caspase-3 activation, specifically in apoptotic signaling upstream of caspase-3 and downstream of c-Jun N-terminal kinases. 238,[241][242][243][244] Second, MMP-3 might potentially be involved in a-synuclein cleavage. Sung et al 245 showed that MMP-3 cleaves purified a-synuclein in vitro and that a-synuclein aggregation increased in the presence of MMP-3-cleaved a-synuclein fragments compared to a solution without these fragments.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…By increasing ROS synthesis, it is likely to participate in the amplification of signals, leading to the activation of the MAPK pathway. Those MAPKs activate the AP-1 transcription factor and upregulate the MMPs [123]. The level of MMP-12 increases after UV exposure [124].…”
Section: Factors That Affect Collagen and Elastin Dynamicsmentioning
confidence: 99%
“…Tetracycline derivatives that penetrate the BBB, such as doxycycline and minocycline, downregulate the MMP-3 expression induced by cell stress, cytokines and other stimuli, with subsequent attenuation of neuroinflammation and apoptosis of dopaminergic neurons, both in vitro and in vivo [407][408][409][410][411]. Other compounds, such as ghrelin (an endogenous ligand for growth hormone secretagogue receptor 1a), exendin-4 (analog of glucagon-like peptide-1) or glycitein (a bacterial metabolite of the isoflavone glycitin) have also been found to attenuate MMP-3 expression, as well as loss of nigrostriatal dopaminergic neurons and hippocampal neurons [412][413][414][415].…”
Section: Therapeutic Strategies For Inhibiting Metalloproteinases In mentioning
confidence: 99%